Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Pada UMKM Tahu Kocek Bang Geo Jember - Dwi S, Lalika Lafiska; Hidayah, M. Taufiq; Puspitasari, Nely; Sintawati, Sintawati; Qomariah, Nurul (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
MSMEs are businesses that drive the national economy. Currently the government is focusing on developing these MSMEs to increase community economic activity. The aim of this research is to find out how the marketing strategy carried out by Tahu Kocek Bang Geo MSMEs increases sales. The type of research is qualitative with SWOT analysis. Data collection methods are interviews, documentation and observation. The results of this research show that the strategic analysis carried out has been effective and the SWOT strategy has been implemented to increase sales at Tahu Kocek Bang Geo MSMEs, namely by adding facilities, promoting various products according to the tastes of the people of Jember. Keywords: Delights, Marketing Strategy, MSMEs, Pocket Tofu Culinary SWOT Analysis.